# Answer on Algebra Question for nks prasad

Question #10309

using factor theorem, show that x-y, y-z are the factors of x9x^2-z^2)+y(z^2-x^2)+z(x^2-y^2)

Expert's answer

x(x^2-z^2)+y(z^2-x^2)+z(x^2-y^2)=x(x-z)(x+z)+y(z-x)(z+x)+z(x-y)(x+y)=-x(z-x)(x+z)+y(z-x)(z+x)+z(x-y)(x+y)=(z-x)(z+x)(y-x)-z(y-x)(x+y)=

=(y-x)((z-x)(z+x)-z(x+y))

=(y-x)((z-x)(z+x)-z(x+y))

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment